COMMUNICATIVE ACTIVITIES IMPLEMENTED BY ENGLISH TEACHERS IN TEACHING ENGLISH - Deka Nur Mahenza; Gita Mutiara Hati (JALL (Journal of Applied Linguistics and Literacy), 2020)
This study aimed at finding out the communicative activities implemented by English teachers in teaching English at grade eleventh of one of the States Senior High Schools in Bengkulu, Indonesia, and the communicative activity frequently implemented by the English teachers. This study used the mixed method design which was the combination of a qualitative and quantitative approach to collect and analyze data. The subject of the research was two English teachers who teach speaking subjects at the school. The instruments used in this research were the observation checklist and interview. The findings found that there were thirteen types of communicative activities that were used by the English teachers. The communicative activity that was mostly used by the teachers was the question and answer session. So, it is concluded that the teachers provided the communicative activities. Then, it is suggested for further researchers to conduct a study with a similar field of this present research, such as communicative activities in listening or reading skills.Keywords: Teaching English, Communicative Activities